2019
DOI: 10.1002/anie.201900763
|View full text |Cite
|
Sign up to set email alerts
|

A General Protocol for C−H Difluoromethylation of Carbon Acids with TMSCF2Br

Abstract: An efficient method for the selective C‐difluoromethylation of carbon acids with the reagent TMSCF2Br has been developed. A variety of structurally diverse sp3‐ and sp‐hybridized carbon nucleophiles, including esters, amides, fluorenes, terminal alkynes, β‐ketoesters, malonates, and other activated C−H nucleophiles, could be efficiently and selectively transformed into the corresponding C‐difluoromethylated products under mild conditions. This protocol is also effective for the late‐stage difluoromethylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 58 publications
0
20
0
2
Order By: Relevance
“…Recently, (bromodifluoromethyl)trimethylsilane (1) which can be readily obtained from the Ruppert-Prakash reagent [14,15], has been introduced as a reagent for the synthesis of various difluorinated compounds [16][17][18]. This silane is very sensitive to Lewis bases and accordingly it was used as a precursor of difluorocarbene, which can react with enol ethers [19,20] (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, (bromodifluoromethyl)trimethylsilane (1) which can be readily obtained from the Ruppert-Prakash reagent [14,15], has been introduced as a reagent for the synthesis of various difluorinated compounds [16][17][18]. This silane is very sensitive to Lewis bases and accordingly it was used as a precursor of difluorocarbene, which can react with enol ethers [19,20] (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Hu and co-workers demonstrated that commercially available TMSCF 2 Br was an efficient reagent for the C-difluoromethylation of a range of C(sp 3 ) and C(sp) nucleophiles, such as esters, amides, fluorenes, terminal alkynes, malonates, b-ketoesters and other activated C-H nucleophiles (Scheme 29C). 129 For this protocol, the authors also propose a difluorocarbene mechanism.…”
Section: C(sp 3 )-Cf 2 H Bond Formation: Electrophilic Difluoromethylationmentioning
confidence: 99%
“…In 2019, Hu and co-workers reported the use of commercially available TMSCF 2 Br as a difluoromethylation reagent for a selection of electron-rich and electron-neutral alkynes under ambient conditions (Scheme 62). 129 Heterocycles such as dibenzothiophene and benzofuran are compatible under the optimised reaction conditions. The authors suggested that a difluorocarbene mechanism is operating.…”
Section: Difluoromethylation Of Alkynesmentioning
confidence: 99%
“…[ 4 ] Hu disclosed an efficient C—H difluoromethylation by using TMSCF 2 Br, a reagent developed by them recently, [ 5 ] as a difluorocarbene source. [ 6 ] Difluorocarbene can also act as a dipolar CF 2 unit for consecutive bond‐forming reactions, [ 7 ] which were described by Dilman. [ 8 ] Outstanding accomplishments have been achieved in the chemistry of difluorocarbene.…”
Section: Background and Originality Contentmentioning
confidence: 99%